Keabsahan Perjanjian Jual Beli yang Tanda Tangan Salah Satu Pihak Berubah dalam Perspektif Hukum Perdata - Mubarak, Ahmad (Journal of Contemporary Law Studies, 2025)
Land holds a crucial dual role: it serves as a social asset that binds community unity and a capital asset fundamental to the economy, trade, and speculation. Human need for land is often met through sale and purchase, where physical and ownership rights are transferred from seller to buyer, accompanied by an agreed payment. However, disputes can arise, as seen in cases of underhand land sales where the seller's signature is contested after phased payments have been made, with the seller subsequently denying the transaction and claiming the signature on the agreement isn't theirsIn this writing, the author uses a normative research type, by examining legal library materials or secondary data by inventorying and analyzing laws and regulations that regulate changes in signatures that are not recognized in the sale and purchase agreement and identifying the problem. According to the findings of this research: Firstly, concerning a signature alteration not recognised by one of the parties in a sale and purchase agreement, this compromises the due diligence in its application. Consequently, the sale and purchase agreement may be annulled as it contravenes the subjective conditions for validity, as stipulated in Article 1320 of the Civil Code. Secondly, the legal recourse available to the aggrieved party is outlined in Article 1877 of the Civil Code. This involves submitting the disputed signature to the court for verification by a judge. Alternatively, such verification can also be pursued through non-litigious channels, specifically by comparing the signature against various other documents.